Polymer Grafting and its chemical reactions - Purohit, Priyank; Bhatt, Akanksha; Mittal, Ravi K.; Abdellattif, Magda H.; Farghaly, Thoraya A. (Frontiers in Bioengineering and Biotechnology, 2023)
Polymer grafting is a technique to improve the morphology, chemical, and physical properties of the polymer. This technique has the potential to improve the existing conduction and properties of polymers other than charge transport; as a result, it enhances the solubility, nano-dimensional morphology, biocompatibility, bio-communication, and other property of parent polymer. A polymer’s physicochemical properties can be modified even further by creating a copolymer with another polymer or by grafting. Here in the various chemical approaches for polymer grafting, like free radical, click reaction, amide formation, and alkylation have been discussed with their importance, moreover the process and its importance are covered comprehensively with their scientific explanation. The present review also covers the effectiveness of the graft-to approaches and its application in various fields, which will give reader a glimpse about polymer grafting and its uses.